Blockchain technology : fundamentals, applications, and case studies - Julie, Golden, 1984-; Nayahi, J. Jesu Vedha; Zaman, Noor, 1972- (Boca Raton, FL : CRC Press, 2021)
"This book presents a detailed exploration of adaption and implementation, as well as a 360-degree view spectrum of blockchain technologies in real-world business applications. Blockchain is gaining momentum in all sectors. This book offers a collection of protocol standards, issues, security improvements, applicability, features, and types of cryptocurrency in, processing and through 5G technology. The book covers the evolution of blockchain from fundamental theories to present forms. It offers diversified business applications with usable case studies and provides successful implementations in cloud/edge computing, smart city, and IoT. The book emphasizes the advances and cutting-edge technologies along with the different tools and platforms. The primary audience for this book includes industry experts, researchers, graduate and under- graduation students, practitioners, and business managers who are engaged in blockchain and IoT related technologies"--
Blockchain and Internet of Things : A survey biography / P.J. Beslin Pajila, E. Golden Julie, S.Gomathi -- A review of protocols and standards / Dr. S.Gomathi, Mabel Finney, PJ Beslin Pajila -- Block chain technology : An insight of architecture, use cases and its application with Industrial IoT and Big data / Mr. K. Suresh Kumar, Dr. A.S. Radhamani, Mr. S. Sundaresan, Dr. T. Ananth Kumar.
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases); TECHNOLOGY / Engineering / General; TECHNOLOGY / Manufacturing